"Any diet will do ya!"… For weight loss, that is. Issue 9 (September 2015) - Benson, Janice L.; Kirley, Kate
Abstract : N/A: Johnston BC, Kanters S, Bandayrel K, et al. Comparison of weight loss among named diet programs in overweight and obese adults: a meta‐analysis. JAMA . 2014; 312(9):923–933.